2013
DOI: 10.1016/j.jval.2013.03.1470
|View full text |Cite
|
Sign up to set email alerts
|

Economic comparison of hemostatic agents in cardiac surgery

Abstract: A283surgical procedures, but also the administration of medicines to control lipids, blood pressure, antidepressants and even hypoglycemia, and even then those expenditures does not consider the indirect expenses such as transportation and escort the patient to the hospital and absence from work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Three studies identified in this review investigated the clinical and economic value of Floseal ® in cardiac and vascular procedures [ 6 8 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies identified in this review investigated the clinical and economic value of Floseal ® in cardiac and vascular procedures [ 6 8 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The third study was an abstract accepted for poster publication at the International Society For Pharmacoeconomics and Outcomes Research in May 2013 [ 8 ] that assessed the economic value of Floseal ® in the US based on the study endpoints and results of the Nasso study [ 7 ] and quantified the monetary costs associated with the efficient control of intraoperative bleeding and contributing complications. If FloSeal ® was the exclusive method used to achieve haemostasis in a hospital performing 600 mixed cardiac surgeries annually, outcomes would be improved and achieved cost savings due to the 242 hours saved in operating room and 33 major and 76 minor complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations